The Influence of Psychological Well-Being, Job Stress, and Job Satisfaction on Employee Performance at PT. Bank Rakyat Indonesia (Persero) Tbk. Pematangsiantar Branch - Chintya Angelica Siahaan; Elperida Sinurat; Junika Napitupulu; Rintan Saragih (Fakultas Ekonomi Universitas Simalungun, 2026)
This study aims to analyze and determine the effect of psychological well-being, work stress, and job satisfaction on employee performance at PT Bank Rakyat Indonesia (Persero) Tbk, Pematangsiantar Branch. The type of research used in this study is quantitative research. The sample in this study consisted of 80 respondents who are employees of PT Bank Rakyat Indonesia (Persero) Tbk, Pematangsiantar Branch. Based on the results of the t-hypothesis test, it can be concluded that psychological well-being partially has a positive and significant effect on employee performance, work stress partially has a positive and significant effect on employee performance, and job satisfaction partially has a positive and significant effect on employee performance. Furthermore, the F-hypothesis test results indicate that psychological well-being, work stress, and job satisfaction simultaneously have a significant effect on employee performance. The value of the coefficient of determination (adjusted R-square) is 0.922. Based on this value, psychological well-being, work stress, and job satisfaction are able to influence employee performance by 92.2%, while the remaining 7.8% is explained by other variables or factors not examined in this study